Higher education and economic development: the importance of building technological capabilities - Kruss, Glenda; McGrath, Simon; Petersen, Il-Haam; Gastrow, Michael (Elsevier, 2015)
Higher education and development has not been a priority of global policy or research funding in recent decades. Yet, since the millennium, Southern governments have become believers in the global knowledge economy and higher education enrolment growth has been phenomenal. In this paper we offer an original account of how higher education institutions contribute to economic development by drawing on evolutionary economics and the national innovation systems approach.